Development of Android-Based Computer-Based Testing (CBT) to Prevent Academic Dishonesty - Narwati, Lily May; Herpratiwi, Herpratiwi; Nurwahidin, Muhammad (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to design and develop an Android-based Computer-Based Testing (CBT) system as a preventive strategy against academic dishonesty in the learning evaluation process. The background of this study stems from the high incidence of cheating during conventional digital exams, which have yet to effectively address the exploitation of technological loopholes by students. The research employed a Research and Development (R&D) approach using a modified Borg & Gall development model through stages including needs analysis, product design, expert validation, limited trials, revisions, and field testing. The developed system features several security measures such as randomized questions and answers, screen locking (kiosk mode), restriction of access to other applications, and monitoring of activities during the exam. Evaluations by subject matter and media experts yielded an average feasibility score of 89%, indicating that the application is highly suitable for use. Meanwhile, trials conducted with high school students showed that the application effectively reduced opportunities for academic dishonesty and received positive user feedback. Therefore, this Android-based CBT system holds strong potential as a technological innovation for conducting fair, efficient, and credible educational evaluations.